A plausible model for bimodal p53 switch in DNA damage response. Issue 5 (31st January 2014) - Sun, Tingzhe; Cui, Jun
Abstract : p53 is a tumor suppressor and the p53 dynamics displays stimulus dependent patterns. Recent evidence suggests a bimodal p53 switch in cell fate decision. However, no theoretical studies have been proposed to investigate bimodal p53 induction. Here we constructed a model and showed that MDM2–p53 mRNA binding might contribute to bimodal p53 switch through an intrinsic positive feedback loop. Lower damage favored pulsing while monotonic increasing was generated with higher damage. Bimodal p53 dynamics was largely influenced by cellular MDM2 and elevated p53/MDM2 ratios with increasing etoposide favor mono‐ubiquitination. Our model replicated recent experiments and provided potential insights into dynamic mechanisms of bimodal switch. Abstract : We first mathematically investigated the bimodal p53 dynamics. We modeled the effect of p53mRNA–MDM2 binding on the dynamics of p53. The bipartite role of MDM2 determines the bimodal p53 dynamics. Intrinsic positive feedback guarantees the monotonic increasing of p53.